The origins of literacy: The Da Vinci code. (Economist, 2010)
Research conducted by cognitive neuroscientist Stanislas Dehaene has found that learning to read may lead to profound changes in the brain's visual system. Dehaene's studies suggest that a small area of the brain that he calls the visual word form area (VWFA) is particularly activated by the written word. He believes that the VWFA evolved for object recognition and is activated both by an object and by that object's mirror image. Dehaene has found that all children make an error he calls “early mirror reading” when learning to read and write, which may happen because these children have to unlearn the earlier survival skill of recognizing mirror images as identical to the object they are depicting. Dehaene and his colleagues have also studied brain responses in literate and illiterate adults, finding that the patterns of activity elicited by visual stimuli depicting faces were different in literate and illiterate brains.